2017
DOI: 10.18632/oncotarget.15766
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequencing analysis reveals protective role of kruppel-like factor 3 in colorectal cancer

Abstract: The Kruppel-like factor (KLF) family of transcription factors plays an important role in embryonic formation and cancer progression. This study was performed to determine the clinical importance of the KLF family in colorectal cancer (CRC). In total, 361 patients with CRC from The Cancer Genome Atlas (TCGA) cohort were used to comprehensively study the role of the KLF family in CRC. The results were then further validated using an in-house cohort (n=194). Univariate and multivariate Cox proportional hazards mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…By comparing the TAMR/MCF-7 cells with the parental cells, transcriptional regulators encoded by LHX and KLF , growth factors encoded by VEGFC, IGF, AGT, TGFA, and HGFAC , cytokines encoded by EDN1 and TIMP2 , G-protein coupled receptor encoded by EDNRA, and transmembrane receptor encoded by BAMBI, enzymes encoded by MYH10 and FLT4, and other genes including LAMA1 and COL, were found to be differentially expressed in our study. Previous studies have shown that the Kruppel-like family of Transcriptional regulators, encoded by KLF genes, regulates not only physiological processes but also the pathogenesis of many diseases, including cancer and inflammatory disorders [ 15 , 16 ]. KLF7, KLF12 and KLF13 were found to be up-regulated in our trascriptome analysis results.…”
Section: Resultsmentioning
confidence: 99%
“…By comparing the TAMR/MCF-7 cells with the parental cells, transcriptional regulators encoded by LHX and KLF , growth factors encoded by VEGFC, IGF, AGT, TGFA, and HGFAC , cytokines encoded by EDN1 and TIMP2 , G-protein coupled receptor encoded by EDNRA, and transmembrane receptor encoded by BAMBI, enzymes encoded by MYH10 and FLT4, and other genes including LAMA1 and COL, were found to be differentially expressed in our study. Previous studies have shown that the Kruppel-like family of Transcriptional regulators, encoded by KLF genes, regulates not only physiological processes but also the pathogenesis of many diseases, including cancer and inflammatory disorders [ 15 , 16 ]. KLF7, KLF12 and KLF13 were found to be up-regulated in our trascriptome analysis results.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, it will now be important to determine how the phased-activity of these novel cell cycle associated transcription factors manifests in the absence of regulation at the level of gene expression. Indeed, the recent findings that levels of ZKSCAN1 modulate hepatocellular carcinoma progression in vivo and in vitro 42 , HES4 expression is linked to osteosarcoma prognosis 43 , and that KLF3 loss correlates with aggressive colorectal cancer phenotypes 44 suggests such understanding could have translational potential. Taken together, our regulon analysis thus confirms, and in several cases extends, understanding of the phase-correlated activity of many transcription factors across cell cycle.…”
Section: Resultsmentioning
confidence: 99%
“…It will now be important to experimentally dissect the roles and importance of these novel factors to proliferating cells, how their activity is precisely controlled across phases, and determine their roles in disease. Indeed, the aforementioned links between ZKSCAN1 levels and hepatocellular carcinoma 42 , HES4 levels and osteosarcoma 43 , and KLF3 levels with colorectal cancer 44 suggests enhanced understanding of these factors in the context of the cell cycle could have translational potential.…”
Section: Discussionmentioning
confidence: 99%
“…KLFs are a family of zinc-nger transcription factors, which are widely expressed in multiple human organs or tissues [21]. KLF family is involved in diverse biological processes, and their abnormal expression may lead to human diseases, like cancer [22]. In oral cancer, several members of the KLFs family had been proved to be implicated in the pathogenesis of the cancers.…”
Section: Discussionmentioning
confidence: 99%